Marx and the Unity of Science - Natural and Social. - Kedrov, B. M. (Russian Studies in Philosophy, 1968)
The question of the unity of scientific knowledge, including that of the unity of the natural sciences and the humanities (social and philosophical sciences), occupies an important place in the writings of Marx. As a consistent materialist, Marx demonstrated that the connection among the sciences was based on an objective connection among the phenomena of nature and society. This outlook provides the key to discovering the unity of the sciences in our own day. Let us see how Marx posed that question, and how it stands today.